Rolling and transient tethering of leukocytes on antibodies reveal specializations of selectins - Chen, Shuqi (The National Academy of Sciences of the USA, 1997)
Antibodies immobilized on the wall of a flow chamber can support leukocyte rolling in shear flow. IgM mAb to Lewis(x) (CD15) and sialyl Lewis(x) (CD15s), which are carbohydrate antigens related to selectin ligands, plus mAb to CD48 and CD59, could mediate rolling. IgM and IgG mAb to L-selectin (CD62L), lymphocyte function-associated antigen 1 (CD11a), CD43, intercellular adhesion molecule 3 (CD50), and CD45 mediated only firm adhesion. In contrast to selectins, antibodies supported rolling only within a restricted range of site densities and wall shear stresses, outside of which firm adhesion or detachment occurred. When wall shear stress was increased, rolling velocity increased rapidly for antibodies but not for selectins. The kinetics of dissociation from the substrate of transiently tethered cells also increased more rapidly as a function of shear stress for antibodies than for selectins. These comparisons emphasize a number of remarkable features of selectins, including the lack of development of firm adhesion, and suggest that specialized molecular or cellular mechanisms must be required to explain their ability to support rolling over a wide range of environmental variables.